Enhancing Educational Equity: An Analysis of the Jakarta Smart Card’s (KJP) Program Impact - Manila, Hanifia Ihza; Gardesh, Awesta; Mangindalat, Rosda Latipa; Saleh, Husny Gibreel Musa (JIAN (Jurnal Ilmiah Administrasi Negara), 2025)
This study explores the impact of the Jakarta Smart Card (Kartu Jakarta Pintar or KJP) program on promoting educational equity among students from low-income families in Jakarta. As a social assistance initiative launched by the Jakarta Provincial Government, the KJP aims to eliminate financial barriers to education by providing monthly financial support to eligible students across elementary, junior, and senior high school levels. Utilizing a literature review approach, this research examines how the program enhances access, affordability, and retention in education. Findings indicate that KJP has significantly contributed to increasing school enrollment, reducing dropout rates, and supporting students' basic educational needs, thereby promoting both horizontal and vertical equity. However, the study also identifies key challenges, including targeting inaccuracies, fund disbursement delays, and limited integration with broader educational quality improvements. While the KJP program demonstrates clear progress toward inclusive education, further policy refinement and systematic evaluation are necessary to maximize its long-term effectiveness and impact. This paper contributes to the broader discourse on educational equity in urban settings and offers insights for policymakers seeking to implement similar financial aid models in other regions.